2017
DOI: 10.1002/ccd.27206
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and clinical performance of polymer‐free biolimus‐eluting stent in patients with ST‐segment elevation acute myocardial infarction in a metropolitan public hospital: The BESAMI MUCHO study

Abstract: In real-world setting, implantation of a new-generation polymer-free BES during STEMI is associated with favorable clinical and angiographic results, pointing toward the overall efficacy and safety of the device in complex clinical scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Stroke was defined as a major ischemic or hemorrhagic cerebrovascular accident resulting in disabling neurological symptoms for at least 24 hr. Repeat target‐vessel revascularization was defined as recurrent ischemic symptoms that resulted in the need for revascularization by either PCI or coronary bypass surgery …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke was defined as a major ischemic or hemorrhagic cerebrovascular accident resulting in disabling neurological symptoms for at least 24 hr. Repeat target‐vessel revascularization was defined as recurrent ischemic symptoms that resulted in the need for revascularization by either PCI or coronary bypass surgery …”
Section: Methodsmentioning
confidence: 99%
“…In total 45 patients with no reflow or slow flow after PCI received intracoronary bolus of glycoprotein IIb/IIIa inhibitors (tirofiban, 10 μg/kg) with a subsequent intravenous infusion (0.15 μg/kg per minute) for 12–24 hr. After the procedure, patients routinely received dual anti‐platelet therapy with aspirin 100 mg and a P2Y12 inhibitor (either clopidogrel 75 mg daily, or ticagrelor 90 twice a day) for 12 months after the primary PCI, and 100 mg aspirin daily was prescribed indefinitely …”
Section: Methodsmentioning
confidence: 99%
“…Over the next three months after restoring TIMI III blood flow through culprit artery with PCI, the primary causes inducing adverse cardiac remodelling can be different from the aforementioned. Indeed, other factors that may contribute to cardiac remodelling after successful primary PCI are arterial healing, vessel remodelling, stent restenosis, thrombosis, and incomplete expansion of stent branches (known as malposition), and stent fracture, which require ischemia-driven target vessel revascularization further [23]. Performing of optical coherence tomography (OCT) in STEMI patients presenting with late and very late stent thrombosis has yielded that stent malposition was determined in 55% cases, quarter of which had been found evidence of positive vessel remodelling [24].…”
Section: Contributing Factors Of Adverse Cardiacmentioning
confidence: 99%
“…3,4 In the large scale LEADERS-FREE trial, a polymer-free biolimuseluting stent (PF-BES) demonstrated improved outcomes as compared to a bare metal stent in high bleeding risk (HBR) patients, when used with a 1-month DAPT strategy. 5 The favorable clinical profile of the PF-BES was further established across a wide range or real-world patients, with outcomes in the lower range of cardiovascular adverse event rates observed with contemporary new-generation drug-eluting stents (DES) when used in patients with mostly non-HBR features, [6][7][8][9] and overall good safety and efficacy when used in patients with mostly HBR features. 10 The PF-BES peculiar characteristics, including the absence of a polymer-coat along with the fast drug elution, may result in rapid and complete stent endothelialization, blunting the late ST risk observed with polymer-coated DESs.…”
Section: Introductionmentioning
confidence: 99%
“…Results: Following PF-BES-PCI, 328(40.3%) and 485(59.6%) patients were discharged with 1-month and longer DAPT (12 months [6][7][8][9][10][11][12]), respectively. Patients with a previous or index MI were less likely to be discharged on 1-month DAPT.…”
mentioning
confidence: 99%